Feed the Future Guatemala Value Chains Project: Summary of impact evaluation study - Hernandez, Manuel A.; Ceballos, Francisco; Paz, Cynthia; Espinoza, Alvaro (International Food Policy Research Institute, 2023)
Guatemala experiences high and continued chronic malnutrition and poverty rates, with a particular concentration around predominantly rural and indigenous areas in the Western Highlands. Agricultural development is similarly low in the region, with farmers generally cultivating small landholdings, showing low agricultural productivity, and having limited ability for capital investment and an overall lack of market opportunities, combined with a relatively weak government support. This brief presents the main findings of the impact evaluation of USAID’s Feed the Future (FTF) Guatemala Value Chains Project that aimed to increase agricultural incomes, strengthen resilience, and improve nutritional outcomes of small farmers and their families in the Western Highlands of the country. The Project was created in 2017, building on the successes and lessons learned from the previous five years of implementation of the FTF Initiative in Guatemala, and relying on four expected results: improving agricultural productivity and diversifying income generation alternatives; expanding access to markets; increasing resilience through implementation of climate-smart and nutrition sensitive agriculture; and strengthening the agriculture and food security enabling environment.